2023
DOI: 10.3389/fneur.2023.1089067
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical and microstructural alterations in bipolar and depressive disorders: A multimodal magnetic resonance imaging study

Abstract: AimsDepression in bipolar disorder (BD) is often misdiagnosed as unipolar depression (UD), leading to mistreatments and poor clinical outcomes in many bipolar patients. Herein, we report direct comparisons between medication-free patients with BD and those with UD in terms of the microstructure and neurometabolites in eight brain regions.MethodsA total of 20 patients with BD, 30 with UD patients, and 20 matched healthy controls (HCs) underwent 3.0T magnetic resonance imaging with chemical exchange saturation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…For instance, NAA levels increased after a pharmacological treatment of HIV [158]. Similarly, lower NAA levels have been observed reliably in people diagnosed with depression [70,81,82], which were normalized by SSRI treatment [159,160]. In the present study, the NAA levels were inversely associated with the PASC group scores on a brief test of recent verbal memory [103], which is broadly consistent with reports of moderate correlations with cognitive ability [161].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For instance, NAA levels increased after a pharmacological treatment of HIV [158]. Similarly, lower NAA levels have been observed reliably in people diagnosed with depression [70,81,82], which were normalized by SSRI treatment [159,160]. In the present study, the NAA levels were inversely associated with the PASC group scores on a brief test of recent verbal memory [103], which is broadly consistent with reports of moderate correlations with cognitive ability [161].…”
Section: Discussionsupporting
confidence: 87%
“…Based on its sensitivity to neuronal dysfunction, NAA has been used as a marker of neuronal integrity, viability, density, and metabolic homeostasis [78,79]. Indeed, reduced NAA has been reliably reported for traumatic brain injury [80], depression [70,81,82], neuroinflammation [83], and a range of brain-based disorders [84].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, in a recent study on ACC, decreased Cr and tCr were found in euthymic BD compared to healthy individuals, while increased PCr and lower Cr/PCr ratio in ACC were associated with greater severity of physical and sexual abuse in the BD group only [ 90 ]. With regard to the PCC, an area with increased tCr in our study in both manic and depressive polarities, few studies are available in BD while data on the metabolite profile of PCC are limited [ 91 , 92 , 93 ]. Previous studies focusing on PCC in BD and unipolar depression groups [ 92 , 93 ] or acutely manic BD and acutely ill patients with schizophrenia [ 89 ] did not find Cr changes in BD.…”
Section: Discussionmentioning
confidence: 98%
“…Given that Cho is considered a marker of phospholipid membrane metabolism, the observed elevated levels in our study probably indicate increased membrane breakdown in PCC and hippocampus in manic and to a lesser degree depressive polarities compared to healthy individuals. In a recent study on BD and unipolar depression, Kong and colleagues reported increased Cho in PCC in the BD group but not in unipolar depression compared to healthy individuals [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this, there are studies assuming that 5-HT3R antagonists provide anti-depressant effects [10,14]. Although the "monoamine hypothesis" is the most accepted theory, recent works have shown an increasing role played by GABA and Glu in the progression of MDD [4,7,10,18] and BD [19]. GABAergic projections are from the hypothalamus (Hyp) to the occipital and parietal cortex, from Hip to PFC and NA and from the thalamus (Thl) to the Ventral Tegmental Area (VTA) [7,10].…”
Section: Introductionmentioning
confidence: 99%